2012
DOI: 10.1890/11-1709.1
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood and habitat effects on vital rates: expansion of the Barred Owl in the Oregon Coast Ranges

Abstract: In this paper, we modify dynamic occupancy models developed for detection-nondetection data to allow for the dependence of local vital rates on neighborhood occupancy, where neighborhood is defined very flexibly. Such dependence of occupancy dynamics on the status of a relevant neighborhood is pervasive, yet frequently ignored. Our framework permits joint inference about the importance of neighborhood effects and habitat covariates in determining colonization and extinction rates. Our specific motivation is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
146
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(152 citation statements)
references
References 53 publications
6
146
0
Order By: Relevance
“…The 2-species approach used in our occupancy analysis allowed us to investigate the effects of Barred Owl presence on colonization and extinction rates of territorial Northern Spotted Owls while accounting for both Barred Owl and Spotted Owl detection rates (Bailey et al 2009, Yackulic et al 2012. Our results suggested that Barred Owls were having substantial negative effects on occupancy dynamics of Northern Spotted Owls, which was consistent with previous findings (Kelly et al 2003, Forsman et al 2011, Sovern et al 2014, Yackulic et al 2014.…”
Section: Barred Owlssupporting
confidence: 88%
“…The 2-species approach used in our occupancy analysis allowed us to investigate the effects of Barred Owl presence on colonization and extinction rates of territorial Northern Spotted Owls while accounting for both Barred Owl and Spotted Owl detection rates (Bailey et al 2009, Yackulic et al 2012. Our results suggested that Barred Owls were having substantial negative effects on occupancy dynamics of Northern Spotted Owls, which was consistent with previous findings (Kelly et al 2003, Forsman et al 2011, Sovern et al 2014, Yackulic et al 2014.…”
Section: Barred Owlssupporting
confidence: 88%
“…In our model, the simplified assumption of the observation process would be relaxed easily because species distribution is calculated as a derived parameter. The effect of local community structure on sampling processes could be incorporated, for example, by altering the definition of species frequency such that species frequency ''near a fixed point'' is influenced or determined by occupancy states of neighboring points (e.g., Bled et al 2011a, b, Yackulic et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these processes (e.g., the dependence on environmental gradients mentioned in the previous paragraph) can be accommodated as relationships defining the probabilities of the community transition matrix as functions of environmental covariates. In addition, the species-specific transition probabilities may be written as time-specific functions of the species composition of the local neighborhood, where the neighborhood is defined by the grid points occurring within some specified distance of the focal point (e.g., Bled et al 2011a, b, Yackulic et al 2012. The motivation underlying such a model is that persistence of a species in a focal grid point may depend on the frequency of this species (rescue effect, Brown and Kodric-Brown 1977) or of competitor species in neighboring points.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the resulting Northern Spotted Owl habitat map performed reasonably well in map accuracy tests (Area Under the Curve (AUC) values of 0.78 to 0.88, and Spearman rank correlations .0.9; ). Thus, while caution is advised when using modeled habitat maps of this sort because it is difficult to derive precise representations of all of the habitat characteristics that are important to a species (Yackulic et al 2012, Loehle et al 2015, we believe that the map that we used in this analysis represented the best available range-wide map of Northern Spotted Owl nesting and roosting habitat.…”
Section: Development Of Covariatesmentioning
confidence: 99%
“…The 2-species approach used in our occupancy analysis allowed us to investigate the effects of Barred Owl presence on colonization and extinction rates of territorial Northern Spotted Owls while accounting for both Barred Owl and Spotted Owl detection rates (Bailey et al 2009, Yackulic et al 2012, 2014. Our results suggested that Barred Owls were having substantial negative effects on occupancy dynamics of Northern Spotted Owls, which was consistent with previous findings (Kelly et al 2003, Forsman et al 2011, Sovern et al 2014, Yackulic et al 2014.…”
Section: Barred Owlsmentioning
confidence: 99%